Pengaruh Implementasi Pelatihan Terhadap Produktifitas Kerja Karyawan di PT. Exedy Manufacturing Indonesia - Ade Sofyan; Pupung Purnamasari; Dendin Jaenudin (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
The present study examines the influence of training program on employee productivity at the production division of PT. Exedy Manufacturing Indonesia in the period of November 2017 to January 2018. The employee productivity is measured using the following regression equation: Y = 20.560 + 0.323 X. The value of Y of 20.560 means that without training program (x = 0), the employee productivity is 20.560. An increase of one unit means that there is an increase in productivity as much as 0.323. The data analysis results in the r value of 0.494, meaning that the training program has a positive effect on employee productivity as much as 0.494. The training program contributes to employee productivity as much as 24.40%; the rest is influenced by factors other than the studied variable. It is also revealed that the observed t is 3.109, higher than the critical t of 2.037, meaning that the training program has an effect on employee productivity at PT. Exedy Manufacturing Indonesia